Determinants of Micro and Small Enterprises Growth in Selected Towns of West Shoa Zone, Oromia Regional State, Ethiopia - Geleta, Negash; Talegeta, Sileshi (International Journal of Small and Medium Enterprises, 2019)
MSEs have an important contribution to economic growth and employment creation in Ethiopia.  However, due to different bottlenecks that hinder the growth, MSEs found in these three towns were not grown as it was expected. Therefore, this study aimed at identifying the major determinants of MSEs growth in West Shoa Zone, Oromia region, Ethiopia. In the study, both qualitative and quantitative research methods were used. Primary data was obtained using questionnaires. Stratified sampling was used to select proportional number of samples from the study area. The study used Chi-square and logistic regression to measure the association and determine growth probability of MSEs, respectively. The result of the study revealed, Entrepreneurial competency, managerial skills, market access, innovation, high initial investment size, access to finance and manufacturing sector variables were identified as a major determinant of growth of the MSEs in the study area.  MSEs Owner/manager characteristics such as gender and age were found not to have an influence on the growth of the enterprises as the descriptive result showed. The probability of growth of MSEs were positively influenced by entrepreneurship competency, management skill, market access, initial investment size, and sector in manufacturing; however, getting access to finance and engaging in innovation activity have negative impact on the growth probability of MSEs based on the binary logit model result.  The variables included in the model explain about 73.38% of the influences on the MSEs Growth so as, the model is fit. The study recommends that proper understanding of these factors constitutes an essential starting point and important for the Owner/manager of MSEs, government and non-governmental organizations to formulate policies and strategies in order to reduce unemployment, poverty and income inequality thereby promote MSEs and their growth in the country and particularly in West Shoa Zone.